Rationales for engaged scholarship projects in one college at a distance institution - Piera Biccard; Soane Joyce Mohapi (Journal of Community Service and Empowerment, 2022)
This article aimed to explore engaged scholarship project leaders’ rationales for starting their engaged scholarship project in communities. Community engagement (or engaged scholarship) has become a required part of the academia and increasingly becoming a scholarly endeavor.  Academics in the education faculty at one university in South Africa were asked to voluntarily participate in a study exploring their rationales for starting their engaged scholarship projects. Semi-structured interviews were held with project leaders. Responses indicated four factors in rationales, firstly, the context selected for project were closely linked to project leader’s early experiences in education, secondly, project leaders selected subjects that were known for being problematic to teach, thirdly, the challenges within the context motivated project leaders to become involved and lastly, project leaders indicated that their motivation to remain involved in the project stemmed from wanting to develop the project further. The study was limited to project leaders in one faculty and only focused on rationales. Engaged scholarship projects are closely intertwined with personal backgrounds. It is recommended that community engagement project leaders reflect on their rationales to build more robust projects.